Physiological MRI for neuropharmacological and advanced cerebral haemodynamic studies - Dewey, Rebecca S. (2012)
This thesis investigates the application of physiological measures made using magnetic resonance imaging (MRI) to study cerebral haemodynamics and the pharmacological modulation of brain activity.